Maze runner : the death cure. - Ball, Wes; O'Brien, Dylan, 1991-; Salazar, Rosa; Scodelario, Kaya, 1992-; Esposito, Giancarlo ([Beverly Hills, CA] : Twentieth Century Fox Home Entertainment, 2018)
In the epic finale to the saga, Thomas leads his group of escaped Gladers on their final and most dangerous mission yet. To save their friends, they must break into the legendary Last City, a WCKD-controlled labyrinth that may turn out to be the deadliest maze of all. Anyone who makes it out alive will get answers to the questions the Gladers have been asking since they first arrived in the maze.
Originally released as a motion picture in 2018.
Special features: Audio commentary by director Wes Ball, screenwriter T.S. Nowlin, producer Joe Hartwick,Jr.; The final run; Allies reunited.℗
Producer, Joe Hartwick, Jr. ; screenwriter, T.S. Nowlin, director, Wes Ball.
Rating: PG-13; for intense sequences of sci-fi violence and action, language, and some thematic elements.
DVD, wide screen (2.39:1); Dolby digital 5.1 (English), Dolby digital 2.0 (Spanish, French), English descriptive audio 5.1.
English, French or Spanish dialogue; French or Spanish subtitles; English subtitles for the deaf and hard of hearing (SDH); Closed-captioned.
Keywords: Adventure films; Science fiction films